NCMP-08. MANAGEMENT OF RADIONECROSIS AFTER STEREOTACTIC RADIATION FOR BRAIN METASTASES IN THE SETTING OF IMMUNE CHECKPOINT INHIBITORS. (5th November 2018) - Jurica, James; Bernicker, Eric; Dalwadi, Shraddha; Tremont-Lukats, Ivo; Butler, Brian; Teh, Bin; Farach, Andrew
Abstract: BACKGROUND: Immune checkpoint inhibitors (ICI) are an increasingly common therapy for metastatic solid tumors. Despite their efficacy, many patients develop brain metastasis requiring stereotactic radiosurgery (SRS) or fractionated stereotactic radiation therapy (SRT). Radiation necrosis (RN) is a known risk. Recent observations suggest that patients receiving SRT/ICI may experience synergism albeit with potential increased risk of symptomatic RN. The best treatment in this setting remains unknown. VEGF inhibitors have demonstrable efficacy in treatment of RN and may be beneficial in treating neurotoxicity associated with combination SRT/ICI. METHODS: Data were analyzed retrospectively from 169 consecutive patients at a single institution undergoing SRS/SRT for brain metastasis from 2015–2017. 10 patients were eligible for evaluation having received SRT and ICI within a 6 month timeframe and with a minimum 3 months survival for assessment of RN. 7 patients were treated for lung adenocarcinoma, 2 for high-grade neuroendocrine tumor, and 1 with triple-negative breast cancer. RESULTS: 10 patients were treated with SRS (90%), SRT (60%), both (50%), or SRS followed by whole-brain radiation (10%) to a total of 65 brain metastases. ICI (nivolumab, pembrolizumab, atezolizumab, ipilimumab) was administered before, during, or after SRS/SRT. 6 patients (60%) developed symptomatic grade ≥ 1 neurological adverse events. Of these 6, 4 (40%) developed grade 3 RN requiring bevacizumab. Symptoms resolved rapidly in 3 of 4 patients (75%), the 4 th patient died of complications of disease shortly after bevacizumab administration. Mean 12 month survival from initial immunotherapy treatment was 89% and mean 18 month survival from initial SRT was 78%. CONCLUSION: Combination treatment with SRT/ICI for brain metastases appears to be associated with high rates of RN compared to historical standards. Given the prolonged survival seen, appropriate management of this complication is paramount. Short course bevacizumab appears highly effective in treating symptomatic RN associated with ICI. Further evaluation with a larger sample size is warranted.